2001
DOI: 10.1002/ijc.1365
|View full text |Cite
|
Sign up to set email alerts
|

Efficient antitumor immunity derived from maturation of dendritic cells that had phagocytosed apoptotic/necrotic tumor cells

Abstract: Dendritic cells (DCs) that acquired antigen from apoptotic tumor cells are able to induce major histocompatibility complex (MHC) class I-restricted cytotoxic T lymphocytes and antitumor immunity. In the present study, we investigated the efficiency of antitumor immunity derived from DCs that had phagocytosed apoptotic/necrotic BL6-10 melanoma cells compared with that of DCs pulsed with the tumor mTRP2 peptide. Our data showed that phagocytosis of apoptotic/ necrotic tumor cells resulted in maturation of DCs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 54 publications
1
120
3
Order By: Relevance
“…It has been demonstrated that exogenous tumor antigens released from apoptotic and necrotic tumor cells can be captured by dendritic cells and presented to CD8 þ T cells through the cross-priming pathway. 34,51,52 Therefore, the AdV TERT mTNF-a gene therapy-induced tumor necrosis may also release OVA tumor antigen, which can be crosspresented by the mouse dendritic cells to CD8 þ T cells. In addition, the hTERT is the rate-limiting component in the telomerase complex and is most closely correlated with telomerase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that exogenous tumor antigens released from apoptotic and necrotic tumor cells can be captured by dendritic cells and presented to CD8 þ T cells through the cross-priming pathway. 34,51,52 Therefore, the AdV TERT mTNF-a gene therapy-induced tumor necrosis may also release OVA tumor antigen, which can be crosspresented by the mouse dendritic cells to CD8 þ T cells. In addition, the hTERT is the rate-limiting component in the telomerase complex and is most closely correlated with telomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…BL6-10 is a murine B16 melanoma cell line with high lung metastasis. 34 The ovalbumin (OVA)-expressing BL6-10 OVA cell line was generated in our laboratory by transfection of BL6-10 cells with transgene OVA and maintained in a Dulbecco's modified Eagle's medium supplemented with 10% fetal calf serum (FCS) and G418 (0.5 mg ml À1 ). 35 L929, a murine fibroblast cell line obtained from American Type Culture Collection (Rockville, MD) was maintained in culture medium Dulbecco's modified Eagle's medium supplemented with 10% FCS, whereas 293, a human embryonic kidney cell line transformed with AdV5 E1 was obtained from Microbix Biosystems (Toronto, ON, Canada) and maintained in culture medium Eagle's minimum essential medium (MEM) supplemented with 10% FCS.…”
Section: Cell Lines Antibodies Cytokines Peptides and Animalsmentioning
confidence: 99%
“…24 Briefly, BM cells prepared from femurs and tibias of normal C57BL/6 mice were depleted of red blood cells with 0.84% ammonium chloride and plated in DMEM plus 10% FCS, GM-CSF (10 ng/ml) and IL-4 (10 ng/ml) on day 1. On day 3, nonadherent granulocytes, and B and T lymphocytes were gently removed, and fresh media were added.…”
Section: Generation Of Transfected Cell Line Mca-26/hsp70mentioning
confidence: 99%
“…The primary MLRs were performed as described previously. 24 Briefly, irradiated BALB/c or C57BL/6 mouse BM-derived DC with phagocytosis of apoptotic MCA or EG7 tumor cells (4000 rad, 0.4 Â 10 5 cells/well) were incubated in graded doses with a constant amount (1 Â 10 5 cells/well) of allogeneic T cells of the C57BL/6 or BALB/c mouse in each well of 96-well culture plates, respectively. After 3 days, T-cell proliferation was measured by adding 1 mCi/ well of [ 3 H]thymidine (1 mCi/ml, Amersham Canada Ltd, Oakville, Ontario, Canada) to cultures and subsequent liquid scintillation counting after an overnight incubation period.…”
Section: Mixed Lymphocyte Reaction (Mlr)mentioning
confidence: 99%
“…As a result, vaccination with immature DCs led to immunologic tolerance to tumorassociated antigens. Therefore, currently used DC vaccination strategies are based on mature DCs that are derived from cultures stimulated by proinflammatory factors TNF-α, CD40 ligand or other factors (11). These mature DCs have potent abilities to stimulate naïve T cells despite of the inhibitory effect of tumor microenvironment (12).…”
Section: Introductionmentioning
confidence: 99%